Metal-free C3 α-aminoalkylation of quinoxalin-2(1H)-ones with amines. (9th November 2021) - Jiang, Xinpeng; Du, Xiaofan; Chen, Keda; Han, Hang; Xu, Di; Zhu, Binbing; Jiang, Le; Fang, Liyun; Yu, Chuanming
Graphical abstract: The first C3 α -aminoalkylation of quinoxalin-2( 1H )-ones with amines under mild conditions. Abstract: An efficient method was developed for the synthesis of various C3 α -aminoalkylated quinoxalin-2(1 H )-ones via Cross-Dehydrogenative Coupling under transition-metal-free conditions, affording the target products with a broad substrate scope in moderate to good yields.